From the History of the Bulgarian Animalistic Lexis. Names of Animals in the Oldest Bulgarian Translation of Aesop’s Fables - Walczak-Mikołajczakowa, Mariola (Poznańskie Studia Slawistyczne, 2021)
Bulgarian works of a non-religious nature began to be written in the 19th century. They popularized a specific vision of a new literary language and contained suggestions of terms from various fields. Sophronius, bishop of Vratsa belonged to the group of writers who significantly influenced the shape of New Bulgarian literary language. By translating Aesop’s fables into a language understandable to Bulgarians, he laid the foundations of Bulgarian animalistic terminology. The author analyses 66 names of animals contained in the fables translated by Sophronius, indicates their origin and the reasons for using a specific term. She further examines which of these terms are still used, and which have become archaisms or have survived only in folk dialects.